2019
DOI: 10.1007/s11301-019-00154-9
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and effects of sustainable CEO compensation: a structured literature review of empirical evidence

Abstract: Sustainability-oriented CEO compensation is being widely discussed among policy makers, corporate practice, and academia. To date, management literature has yielded a growing body of empirical results on the determinants and effects of sustainable CEO compensation. Primarily, empirical studies analyze whether and to what extent sustainability-related issues determine the design of sustainable CEO compensation and how sustainability-oriented CEO compensation impacts corporate performance. However, the scattered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 133 publications
4
63
0
Order By: Relevance
“…Non-financial components in a firm's management compensation (e.g., Davila & Venkatachalam, 2004;O'Connell & O'Sullivan, 2014) are also given more importance in business practice, according to legitimacy and stakeholder theory. Sustainability management goals or management incentives, such as the recognition of social and environmental goals in compensation contracts, should increase the motivation of top managers to adopt IR with an appropriate level of quality (Winschel and Stawinoga 2019). While research on the effects of audit committee composition (e.g., effectiveness, size, expertise, independence, etc.)…”
Section: Content-related Implicationsmentioning
confidence: 99%
“…Non-financial components in a firm's management compensation (e.g., Davila & Venkatachalam, 2004;O'Connell & O'Sullivan, 2014) are also given more importance in business practice, according to legitimacy and stakeholder theory. Sustainability management goals or management incentives, such as the recognition of social and environmental goals in compensation contracts, should increase the motivation of top managers to adopt IR with an appropriate level of quality (Winschel and Stawinoga 2019). While research on the effects of audit committee composition (e.g., effectiveness, size, expertise, independence, etc.)…”
Section: Content-related Implicationsmentioning
confidence: 99%
“…Executive compensation usually takes the form of a fixed-cash salary (i.e., non-incentive-based compensation), incentivebased (i.e., variable) payments (e.g., earnings-related bonus, stock options), and other types of compensation (e.g., severance agreements; Kovermann and Velte 2019). In light of the increased influence and power of the CEO, it is quite common for empirical research to examine CEO compensation while neglecting other executives (Winschel and Stawinoga 2019). Several other board variables were identified in our literature review, including expertise on the board and specific committees and board independence, which indicate high corporate governance quality, as well as CEO power and co-opted boards, which indicate low corporate governance quality.…”
Section: Datamentioning
confidence: 95%
“…As stakeholders criticized short-term orientation in management compensation contracts after the financial crisis of 2008-2009, clawbacks should promote top management incentives to rely on a more long-term and ethical behavior, as they may be punished for future events that conflict stakeholders' interests. Thus, future research designs should consider diversity variables (e.g., gender, nationality, age) or address the implementation of non-financial goals in management compensation contracts (Winschel and Stawinoga 2019;Obermann and Velte 2018).…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…For that reason, future studies could consider professional managers as participants in the experiment. Finally, future studies may consider a qualitative research method as an alternative method as it is also suggested by Winschel & Stawinoga (2019). A qualitative research method may serve to provide richer information.…”
Section: The Effect Of Compensation and Religiosity On Managers' Csr mentioning
confidence: 99%